Evolução molecular do DNA satélite 1.688 em espécies de Drosophila com genomas sequenciados - Leonardo Gomes de Lima (2013)
The 1.688 satellite DNA(satDNA) family, present in species of Drosophila from the melanogaster subgroup, has been used as an important model in several studies about satDNA organization, function and evolution. Nevertheless, most previous studies of this satDNA were restricted to the analysis of just a few copies (less than ten), contrasting with its great abundance in the genome (for instance, 15,000 copies in D. melanogaster). In view of the availability of sequenced genomes of several Drosophila species, including five from the melanogaster subgroup, we aimed at studying the variation, genomic distribution and evolution of the 1.688 satDNA through the analysis of this vast sequence repertoire. Data mining of 1.688 sequences in the Drosophila genomes databases led to the identification and characterization of 6,849 copies of this satDNA in five species of Drosophila of the melanogaster subgroup. Phylogenetic analyses allowed the classification of the copies as euchromatic or heterochromatic for all the species. We report for the first time the presence of several arrays of the 1.688 satDNA in the euchromatin of D. simulans, D. sechellia, D. yakuba and D. erecta. The euchromatic location of each array was confirmed by the analysis of their flanking sequences. Our data revealed that the 1.688 satDNA was present in both chromatin domains in the ancestral species of the melanogaster subgroup. Analyses of the heterochromatic copies yielded detailed information on the copy variations in each species. The intraspecific variation among 1.688 heterochromatic copies was lower than the interspecific one in the species of the melanogaster subgroup, evidencing a pattern of concerted evolution. Nevertheless, the phylogenies obtained with the 1.688 copies were not in total agreement with the species phylogenetic relationships, pointing to different evolution rates. Surprisingly, four 1.688 copies were also found in the genome of D. willistoni, a distantly related species of the melanogaster subgroup. The discontinuous phylogenetic distribution and high nucleotide similarity among the 1.688 copies of D. melanogaster and D. willistoni suggest that the copies of D. melanogaster were introduced in D. willistoni through a horizontal transfer (HT) event. There are no previous reports of HT involving satellite DNAs. Several hints that this event was mediated by a non-LTR retrotransposon called Doc characteristic of D. melanogaster were also found.